Penerapan Pendidikan Agama Islam Melalui Budaya Religius (Application of Islamic Relegios Education Through Religios Cultural) - Ririn Suriani Siregar (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
The education system of Islamic Religion in is a form of elaboration of the mandate of Act No. 20 of 2003 on National Education System, in order to prepare students to be a man of faith and piety and morality, but in practice they have drawn criticism from the public that PAI in school during is rated only equip learners only religious knowledge (cognitive) less emphasis on the aspect of practice (affective andpsychomotor).Where necessary the development of PAI itself, so that PAI is not only limited knowledge but also can be practiced in everyday life either at school or in everyday environments. Either by teachers, and students. Therefore, it is necessary to build a culture of religious (religious culture) in religious activities in schools to improve the practice of affective so in tune with our educational goals.The quality of education will be achieved, if it is supported by all who are organized education component with all considerations. Some of those components are inputs, processes, and outputs, and need full support from those who have an important role in educational institutions. But one thing that is the focus here is that it is very important for education to implement religious values into independent education by using religious culture in its daily application so that students or society remain morally Islamic every day and to always remember Allah swt. Kata kunci: Pendidikan; Religi ,dan Islam Budaya Keagamaan (Budaya keagamaan)